Bauhaus diaspora and beyond transforming education through art, design and architecture - Goad, Philip 19XX-; Stephen, Ann; McNamara, Andrew; Edquist, Harriet 19XX-; Wünsche, Isabel 1965- (The Miegunyah Press, 2019)
Bauhaus Diaspora and Beyond: Transforming Education through Art, Design and Architecture presents an extraordinary new Australasian cultural history. It is a migrant and refugee story: from 1930, the arrival of so many emigre, internee and refugee educators helped to transform art, architecture and design in Australia and New Zealand. Fifteen thematic essays and twenty individual case studies bring to light a tremendous amount of new archival material in order to show how these innovative educators, exiled from Nazism, introduced Bauhaus ideas and models to a new world. As their Bauhaus model spanned art, architecture and design, the book provides a unique cross-disciplinary, emigre history of art education in Australia and New Zealand. It offers a remarkable and little-known chapter in the wider Bauhaus venture, which has multiple legacies and continues to inform our conceptions of progressive education, creativity and the role of art and design in the wider community
Keywords: Rezeption; Bauhaus; Australien; Neuseeland; Australian; Bauhaus / Influence; Art / Study and teaching / Australia / History / 20th century; Art / Study and teaching / New Zealand / History / 20th century; Bildband